An Existence Of Compensation Money For Workers At The End Of STWA - Ummah, Alfin Aslichatul; Wijayanti, Asri (Faculty of Law, University of Muhammadiyaha Surabaya, 2022)
There are many entrepreneurs who do not carry out compensation at the end of Specific Time Work Agreement (STWA). It was resulted in the rights of workers being fully protected. This research aimed to determine the existence for workers with STWA status and their legal remedies. This research was normative juridical with a per-law approach. The results showed that the entrepreneur was obliged to provide compensation money of one month, after the worker completes the contract period for one year. If the working time was less than one year, it would get the right proportionally. Violation of improper payment of compensation money, may be threatened with administrative sanctions. The legal remedy that can be made if the worker does not receive compensation money at the end of the STWA is that the worker can make bipartite negotiations. If it failed, the workers made mediation efforts to the local Department of Labor. If the mediator’s recommendation was not implemented, the worker can file a lawsuit with the Industrial Relations Court. The resulting recommendation was that the Department of Labor should provide more oversight of the registration of the STWA and the enforcement of the compensation payment clause Keywords: STWA, Compensation Money, Employment.